Degradable Natural Lacquer (Urushi) Adhesives Using a Reversible Polymer Based on Hemiaminal Dynamic Covalent Networks. Issue 23 (20th June 2018) - Jung, Jiyoon; Cho, Hye Jin; Kim, Dongyoung; Hwang, Seung Sang; Won, Jongok
Abstract: We have developed a thermally cured, natural lacquer (urushi)‐based adhesive, which has a reversible polymer (RP) additive that promotes degradability. The RP was prepared by thermally treating a hemiaminal dynamic covalent network (HDCN) organo‐gel. The urushi was crosslinked polymer from the curing reaction of urushiol. The main component of the natural lacquer is urushiol, which is the mixture of catechol derivatives containing alkyl side chains. The catechol group has a high adhesiveness, and the long alkyl chains provide high mechanical strength and flexibility. The thermal curing reaction occurred mainly between unsaturated C=C groups in the side alkyl chains of urushiol, and the rate of the curing reaction increased at higher temperature. HDCN was prepared via a reaction between formaldehyde and poly(propylene glycol) bis(2‐aminopropyl ether) in 1‐methyl‐2‐pyrrolidinone. Hexahydrotriazine‐like RP, which is reversible in strong acid solution, was formed after heat treatment. Urushi/RP adhesives were degradable, and the degradation was investigated by tensile strength measurements. The tensile strength increased with increased RP in the urushi/RP adhesives because RP has a higher tensile strength than urushi. The tensile strength of the urushi/RP adhesives decreased by more than one order of magnitude after the material was immersed in 0.5 M of H2 SO4 for 6 h, and the degradability increased with increased RP content. Abstract : Degradable thermoset adhesive using natural urushi and a reversible polymer (RP) was developed. The tensile strength increased with increased RP in the urushi/RP adhesives. The presence of RP allowed for efficient degradation, and the efficiency increased with the amount of added RP. This controlled degradation process allow for the easy removal of an adhesive without leaving damage on the surface of the bonded material when retreatment is needed.